2017
DOI: 10.1177/0022146516685370
|View full text |Cite
|
Sign up to set email alerts
|

Social Disadvantage, Severe Child Abuse, and Biological Profiles in Adulthood

Abstract: Guided by the stress process model and the life course perspective, we hypothesize: (a) that childhood abuse is concentrated, in terms of type and intensity, among socially disadvantaged individuals, and (b) that experiencing serious abuse contributes to poor biological profiles in multiple body systems in adulthood. Data come from the Biomarker Subsample of Midlife in the US. We used latent class analysis to identify distinct profiles of childhood abuse, each reflecting a combination of type and severity. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 88 publications
(141 reference statements)
0
29
0
Order By: Relevance
“…The measure of lifetime trauma utilized in this study also has various limitations, including its retrospective nature and the assessment of childhood abuse and other traumatic experiences occurring many years apart. However, evidence supports the validity and cross-time stability of retrospective reports of childhood abuse (Hardt & Rutter, 2004; Yancura & Aldwin, 2009), including in the MIDUS survey (Lee et al, 2017). As noted, the measure of cumulative trauma exposure is similar to measures in several health-related investigations (Krause et al, 2004; Puterman et al, 2016; Turner & Lloyd, 1995) but reflects a broader conceptualization and less precision than in others that have utilized structured clinical interviews (Hendrickson et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The measure of lifetime trauma utilized in this study also has various limitations, including its retrospective nature and the assessment of childhood abuse and other traumatic experiences occurring many years apart. However, evidence supports the validity and cross-time stability of retrospective reports of childhood abuse (Hardt & Rutter, 2004; Yancura & Aldwin, 2009), including in the MIDUS survey (Lee et al, 2017). As noted, the measure of cumulative trauma exposure is similar to measures in several health-related investigations (Krause et al, 2004; Puterman et al, 2016; Turner & Lloyd, 1995) but reflects a broader conceptualization and less precision than in others that have utilized structured clinical interviews (Hendrickson et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Sociodemographic covariates included gender and race (White vs. minority race/ethnicity). We controlled for parental education (highest level achieved by either parent, measured on a 12-point scale from “no school/some grade school” to “advanced graduate/professional degree”) given that lower family SES is associated with greater odds of various ACEs (Lee, Coe, & Ryff, 2017). Similarly, we adjusted for adult SES as a potential confounder.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have focused on family affluence and sexual abuse in adolescence. Some have found a higher risk of sexual abuse reported by the least affluent adolescents [10,11], whereas one study reported no significant difference in childhood sexual abuse rates between non-poor and poor families [15]. The difference in these findings could stem from differences in the research methodology, as Oshima et al’s data [15] come from childhood sexual abuse reports to the child protective services.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies amongst older adolescents also state higher prevalence because of higher rates of dating violence and peer assault [5,6]. All the studies mentioned above report girls experiencing sexual abuse at higher rates than boys, with girls experiencing three to five times the rate of sexual abuse, compared to boys [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation